Strategi Eksistensi Media Lokal Kotomono.Co Di Tengah Maraknya Media Arus Utama Di Pekalongan - Ana, Lia Afi (ARKANA: Jurnal Komunikasi dan Media, 2025)
Kotomono.co is an information media company that produces journalistic products in the form of opinions and essays. The color of the writing is full of criticism and arguments related to social phenomena. However, its presence amid society with practical and fast media preferences requires kotomono.co to maintain its existence amidst the media preferences inherent in the Pekalongan community. This study aims to determine the strategy used by Kotomono.co in maintaining its existence amidst the many other information media that are more popular in Pekalongan. The analysis process was carried out using descriptive qualitative methods and data collection techniques in the form of interviews, observations, and documentation. The results of the study showed that kotomono.co uses a content strategy, a wide distribution of contributors, and external backlinks.